Early Enteral Nutrition May Improve Survival in Patients With Cardiogenic Shock - Liangliang Zheng; Jingwei Duan; Baomin Duan (Emergency Medicine International)
Conclusion: EEN was not associated with harm, but rather with improved survival outcomes in patients diagnosed with CS. Further studies are required to verify these findings.